Kepribadian Tokoh Utama dalam Novel Maryam karya Okky Madasari - Deswita Kemala Sari; Nurizzati Nurizzati (Persona: Kajian Bahasa dan Sastra, 2023)
The research aims to describe: first, the personality of the main character in Okky Madasari's novel Maryam; second, the factors that influence the formation of the main character's personality in the novel Maryam by Okky Madasari. This type of research is literary research using descriptive methods. The data in this study are words, phrases, clauses and sentences related to the personality of the main character and in the form of a narrator who shows the personality of the main character in the novel Maryam by Okky Madasari. The data collected in this study were then analyzed with the following steps: (1) classifying the data, (2) interpreting the data and (3) making conclusions based on the research results. There are two findings in this study. First, the personality of the main character in the novel Maryam by Okky Madasari, namely (a) low self-esteem, that is, not being able to defend those they love; disappointed, angry; regret; doubt and fear, childlessness; (b) superior, namely trying to get the blessing of both parents and finding the missing family; (c) lifestyle, namely women who are beautiful, intelligent and friendly; (d) creative self, namely developing a packaged milk business and giving the name of their child originating from Lombok; (e) the apparent goal of wanting to have a happy family; (f) social interest, namely caring for Ahmadiyah victims; (2) factors that influence the formation of Maryam's personality, namely (1) genetic factors (innate), and (2) community environmental factors, (3) family environment. The dominant factor is the environmental factor of society and family.